2016
DOI: 10.1186/s12913-016-1796-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of power and actor relations on priority setting and resource allocation practices at the hospital level in Kenya: a case study

Abstract: BackgroundPriority setting and resource allocation in healthcare organizations often involves the balancing of competing interests and values in the context of hierarchical and politically complex settings with multiple interacting actor relationships. Despite this, few studies have examined the influence of actor and power dynamics on priority setting practices in healthcare organizations. This paper examines the influence of power relations among different actors on the implementation of priority setting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…As a result, a highly dynamic policy environment has emerged where actors differ substantively in their interpretations of the country's UHC values and priorities. This reflects existing priority-setting studies in Kenya that have found variances in the way different stakeholders perceive health systems decisions in the country [16,26]. We postulate that stakeholders' articulated values are aligned to their dogmatic principles and their depth of interaction with the country's health and political systems.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As a result, a highly dynamic policy environment has emerged where actors differ substantively in their interpretations of the country's UHC values and priorities. This reflects existing priority-setting studies in Kenya that have found variances in the way different stakeholders perceive health systems decisions in the country [16,26]. We postulate that stakeholders' articulated values are aligned to their dogmatic principles and their depth of interaction with the country's health and political systems.…”
Section: Discussionsupporting
confidence: 76%
“…Given the intrinsically participative nature of health priority-setting, the inclusion of a broad range of stakeholders is essential for the success of UHC in the Kenyan context [24]. Indeed, the multiplicity of stakeholder interests and values has been highlighted in various studies investigating the political economy of various health systems reforms in the Kenyan healthcare sector [16,25,26]. As such, it is imperative to identify and consider the ideological positions of key policy stakeholders when considering Kenya's ideal path towards UHC.…”
Section: Introductionmentioning
confidence: 99%
“… 18 In district hospitals, meanwhile, hard budget choices had to be made to support continued service delivery given the funding challenges. Barasa et al 15 16 27 report experiences from two hospitals. In one ( box 1 ), a dedicated leader adopted inclusive and deliberative decision-making processes—generating wide-ranging staff commitment to the budget priorities set collectively and strengthening the collective sense of staff duty to the hospital and its patients.…”
Section: Resultsmentioning
confidence: 99%
“…These collaborations have provided the foundation for a range of interlinked analyses. 15–18 For each site, ethical approval was obtained from relevant national authorities and also from the London School of Hygiene and Tropical Medicine.…”
Section: Methods: Learning Site Settings and Our Analytic Approachmentioning
confidence: 99%
“…In both instances, these committees were seen as passive, disempowered bodies that merely approved hospital decisions. Several factors contributed to this, including: the power relations between hospital staff; hospital managers' convictions that community members were ill-equipped (illiterate, uneducated, unable to understand budgets, and too narrowly focused on personal experiences) to play a useful role; and as a result, this affected managers' power to minimise community engagement; managers' failure to interrogate whom from the community participated; and the consequent potential for elite community representatives to benefit from the information shared in committee meetings (Barasa et al 2016).…”
Section: Empowermentmentioning
confidence: 99%